Use of XTL fuel as an alternative to conventional diesel fuel: a comprehensive review in the context of european environmental standarts - Kitsenko, Petro (National Technical University "Kharkiv Polytechnic Institute", 2025)
This paper presents a detailed analytical review of existing research and European experiences regarding synthetic diesel (XTL fuels) as a sustainable and environmentally friendly alternative to conventional diesel fuel. The review emphasizes emission reductions, fuel compatibility, infrastructure adaptability, and the socio-economic implications of adopting XTL fuels in Ukraine within the framework of European environmental standards and policies.
Keywords: XTL fuel; synthetic diesel; alternative fuels; emissions reduction; environmental standards; fuel compatibility; infrastructure adaptation; Ukraine-EU integration